PERANCANGAN MEDIA PROMOSI KAPAS KRAMPUNG PLAZA (KAZA) SURABAYA BERBASIS 3D GUNA MENINGKATKAN BRAND AWARENESS - Ananta, Ardy Kusuma (Jurnal Art Nouveau, 2014)
Abstract: At this time the shopping center is very crowded because to fulfill the needs that support their lifestyle or the consumer of the visitors. Of course a mall should look attractive in terms of interior and exterior that got attention of consumers who want to shop. The purpose of this design is to visualize the interior of KAZA CITY Surabaya and to promote through the promotion media of Kapas Krampung Plaza (KAZA) Surabaya in order to improve the brand awareness. The design is done with the approach of the survey, interviews and existing studies in order to formulate the concept of design. The data is analyze using indicators: STP, Strenght, weakness, opportunity, threat and USP (Unique Selling Proposition). From the result of the analysis and the design of the paper found that uniqueness of Kapas Krampung Plaza not yet looked at ppromotion media used. The lack of uniformity of design concept in every media promotion led to a promotion that has been done has a low level of awareness. In this media promotion design of Kapas Krampung Plaza designed to reproduce the uniqueness and the concept of belonging as well as consistent on every media promotion. The design of the work refers to the principles of design and how to create brand awarness with consistency of design. The design is expected to give the design a design in accordance with the concept of Kapas Krampung Plaza as well as improving brand awarness. Â Keywords: Interior, Media Promotion, Brand awareness